2011
DOI: 10.1111/j.1447-0756.2010.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurement of cervical length and risk of preterm delivery

Abstract: Women with threatened preterm labor and a cervical length of <15 mm at presentation are at high risk of delivering preterm within 7 days. Sonographic measurement of cervical length helps to avoid over-diagnosis of preterm labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
4
0
4
Order By: Relevance
“…3,4,12,17,18 Although cervical length is independently associated with the risk of preterm delivery in women with preterm labor, there are conflicting results with regard to the predictive value of cervical length for preterm delivery in this group of patients. Possible explanations for this observation include the relatively small sample size 4,12,18 and differences in the cervical length thresholds used.…”
Section: Discussionmentioning
confidence: 94%
“…3,4,12,17,18 Although cervical length is independently associated with the risk of preterm delivery in women with preterm labor, there are conflicting results with regard to the predictive value of cervical length for preterm delivery in this group of patients. Possible explanations for this observation include the relatively small sample size 4,12,18 and differences in the cervical length thresholds used.…”
Section: Discussionmentioning
confidence: 94%
“…Cervical length is another important prognostic parameter in the preterm delivery ( 11 ) . Cervical length did not correlate with the latency period in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported different uterine cervical length in pregnancy in the same weeks and months. [ 6 12 13 14 15 16 ] On the other hand, the cervical length can be affected by parity, age, gestational age, race, and populations. [ 14 17 ] Therefore, it is appropriate to define a nomogram of mean uterine cervical lengths and their standard deviations for every week of gestation in order to detect deviations from the normal range clinically, determine preterm labor, perform cerclage, prevent unnecessary tocolysis, reduce time of hospitalization, and to indicate lung maturation treatment more precisely based on the uterine cervical length as early as possible.…”
Section: Introductionmentioning
confidence: 99%